The effect of prothrombin, the precursor of thrombin, on the proliferation and migration of colorectal cancer cells - Cumbo, Marija; Dunjić Manevski, Sofija; Gvozdenov, Maja; Mitić, Martina Mia; Đorđević, Valentina; Tomić, Branko (Archives of Biological Sciences, 2024)
Paper description: Thrombin influences cancer growth and progression. Although its precursor, prothrombin, is predominantly expressed in the liver, thrombin can be present in the tumor microenvironment. We examined the expression of prothrombin in selected colorectal cancer cell lines and its effect on these cells by treating them with different prothrombin concentrations and monitoring cell proliferation and migration. All analyzed cell lines expressed prothrombin, with prothrombin exerting an effect on cell proliferation and migration. Prothrombin could impact colon cancer development. Further research into prothrombin’s potential as a diagnostic and therapeutic biomarker is proposed. Abstract: Thrombotic disorders are some of the main comorbidities in cancer patients. So far, research has indicated that thrombin, a key regulator of hemostasis, contributes to cancer progression. However, data on its origin in tumor microenvironments remain elusive. Based on previous research, we analyzed the RNA and protein expression of prothrombin, a precursor of thrombin, in selected colorectal cancer (CRC) cell lines. Since the effect of prothrombin in cancer development has not been previously reported, we treated the cells for 24 h and 48 h with different prothrombin concentrations and assessed the effect on cell proliferation and migration. Our results show that the tested CRC cell lines expressed prothrombin and that prothrombin inhibited proliferation and migration. The presented results suggest that prothrombin may contribute to CRC etiopathology and could serve as a potential diagnostic biomarker and therapeutic target. The mechanisms underlying prothrombin expression in cancer cells, potential prothrombin activation, and the underlying processes driving the described effects warrant further investigation.